Investigating the moderating role of anticipatory guilt on the consumption of luxury brands - Chuah, Joe Soo (Curtin University, 2015)
This study examines how attitudes towards sweatshops, social norms and perceived behavioural factors influence consumers' purchase intention towards luxury branded apparel made in sweatshops and ultimately the willingness to pay more for luxury branded apparel not made in sweatshops. Anticipatory guilt is also tested as a moderator to examine the relationship between intention not to purchase luxury branded apparel made in sweatshops and the willingness to pay more for luxury apparel not made in sweatshops.